IL-1β expression driven by androgen receptor absence or inactivation promotes prostate cancer bone metastasis - DiNatale, Anthony; Worrede, Asurayya; Iqbal, Waleed; Marchioli, Michael; Toth, Allison; Sjöström, Martin; Zhu, Xiaolin; Corey, Eva; Feng, Felix Y; Zhou, Wanding; Fatatis, Alessandro (Cancer Research Communications, 2022)
We report the inverse association between the expression of androgen receptor (AR) and interleukin-1beta (IL-1β) in a cohort of patients with metastatic castration resistant prostate cancer (mCRPC). We also discovered that AR represses the IL-1β gene by binding an androgen response element (ARE) half-site located within the promoter, which explains the IL-1β expression in AR-negative (ARNEG) cancer cells. Consistently, androgen-depletion or AR-pathway inhibitors (ARIs) de-repressed IL-1β in ARPOS cancer cells, both in vitro and in vivo. The AR transcriptional repression is sustained by histone de-acetylation at the H3K27 mark in the IL-1β promoter. Notably, patients' data suggest that DNA methylation prevents IL-1β expression, even if the AR-signaling axis is inactive. Our previous studies show that secreted IL-1β supports metastatic progression in mice by altering the transcriptome of tumor-associated bone stroma. Thus, in prostate cancer patients harboring ARNEG tumor cells or treated with ADT/ARIs, and with the IL-1β gene unmethylated, IL-1β could condition the metastatic microenvironment to sustain disease progression.
Keywords: Humans; Male; Animals; Mice; Receptors, Androgen/genetics; Interleukin-1beta/genetics; Androgens; Prostatic Neoplasms/genetics; Signal Transduction/genetics; Bone Neoplasms/genetics; Tumor Microenvironment